Territorializing policies or generating territorial polices, practical reflexions - Gallicchio, Enrique (2013)
The working hypotheses are three: Local development is a political strategy of change. We are not speaking of a new paradigm, methodology, or a new scholarly theoretical framework, but by contrast, a political change strategy. In this sense we are in front of an instrument that is more ¨social political¨ than ¨technical¨, strictlyspeaking.Given what has already been stated, and the experience of Latin America it is necessary to debate around territorializing policies vs. policies that are territorialized. Two main issues arise, on the one hand, the influence of territory throughout the entire process of local policy making (agenda setting, formulation, implementation,monitoring and evaluation), and what it means to defend ¨territorial sovereignty¨ in articulating strategies.Finally, that the space to go in depth in terms of generation of territorial policies (the raison d etre of a political strategy) demands action in multilevel governance (local, regional, national), local economic development and social capital.